1987
DOI: 10.1029/gb001i004p00297
|View full text |Cite
|
Sign up to set email alerts
|

The National Oceanic and Atmospheric Administration Wp‐3d Meteorolgical, Aerosol, and Gas Systems, and flight operations, on Watox‐86

Abstract: A National Oceanic and Atmospheric Administration WP‐3D meteorological research aircraft was instrumented with a wide range of gas and aerosol sampling equipment to conduct a component of the Western Atlantic Ocean Experiment (WATOX‐86) intensive study. The added instrumentation provided for measurements of condensation nuclei, aerosol scattering extinction, ozone, soot carbon, NOx, SO2, H2O2, NO2, peroxyacetyl nitrate, CO, HNO3, and aerosol particle size/number. Discrete air samples were collected in both gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Aircraft studies of peroxides in mid to high‐latitude regions are limited [ Heikes et al , 1996a; Schnell et al , 1987; Schnell , 1984]. These studies have shown, however, that maximum peroxide mixing ratios are found around 2 km and that mixing ratios generally decrease with latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft studies of peroxides in mid to high‐latitude regions are limited [ Heikes et al , 1996a; Schnell et al , 1987; Schnell , 1984]. These studies have shown, however, that maximum peroxide mixing ratios are found around 2 km and that mixing ratios generally decrease with latitude.…”
Section: Introductionmentioning
confidence: 99%
“…The western Atlantic Ocean is the sink for substantial amounts of air pollution advected eastward from North America. The concentration and composition of these pollutants in the air have been measured [Chen and Duce, 1983;Meinert and Winchester, 1977;Wolff et al, 1986;Sievering et al, 1987] and the amounts scavenged by precipitation studied [Church et al, 1982 The instrumentation on the aircraft is discussed by Schnell et al [ 1987]. The aerosol and ozone data in this report were produced by a General Electric CN counter, a Meteorology Research, Incorporated, nephelometer model 1591, a Dasibi ozone monitor, Particle Measuring Systems active scattering aerosol spectrometer probe (ASASP) 100X and forward scattering spectrometer probe (FSSP) aerosol spectrometers.…”
Section: Introductionmentioning
confidence: 99%